Modified Western blotting for insulin and other diabetes-associated peptide hormones - Naoyuki Okita (Nature Portfolio, 2017)
Abstract Now, the quantification of proinsulin/insulin contents within organisms tends to be evaluated only by enzyme-linked immunosorbent assay (ELISA), although assessing the adequacy of results by some quantification method is important. Remarkably, few scientific papers use detection by Western blotting (WB), another immunological assay, of proinsulin/insulin. We found two problems with quantification of insulin and proinsulin by general WB: the shape of an insulin band in gel electrophoresis is distorted, and the retention potency to a blotting membrane of the peptide hormones (mainly insulin) is low. We solved the first problem by optimizing the sodium dodecyl sulfate concentration in the sample buffer and the second problem by glutaraldehyde fixation following treatment with a blocking solution for a short time. The improvements were confirmed by quantification of proinsulin/insulin in standards, MIN6c4 cell lysates, and MIN6c4 culture supernatants. Furthermore, we showed that the modified WB is applicable to other diabetes-associated peptide hormones: insulin analogs, glucagon, GLP-1s, somatostatins, ghrelins, and pancreatic polypeptide. Our data showed that the modified WB can contribute to qualitative or quantitative analyses of diabetes-associated peptides by providing analytical information based on electrophoresis, although ELISA, which is an almost exclusive method in the quantification of peptide hormones, supplies only numerical data.